?-type fractional Sturm-Liouville Coulomb operator and applied results - Ozarslan, Ramazan; Ercan, Ahu; Bas, Erdal (Wiley, 2019)
In this article, beta-type fractional Sturm-Liouville Coulomb operator is considered by Hilfer fractional derivative. Fundamental spectral theory is investigated for the aforementioned problem. In this context, it is shown that the operator is self-adjoint, eigenfunctions correspond to the distinct eigenfunctions are orthogonal, and eigenvalues are real. Furthermore, applications of this problem are given by the Adomian decomposition method and the results are shown with visual graphs.
Keywords: asymptotic formula; difference equation; eigenfunction; kernel; Sturm-Liouville